Network pharmacology-based analysis of the anti-hyperglycemic active ingredients of roselle and experimental validation. (February 2022) - Niu, Bingxuan; Xie, Xu; Xiong, Xiaoming; Jiang, Junlin
Abstract: Diabetes mellitus is one of the top four leading causes of death among noncommunicable diseases worldwide, according to the World Hibiscus sabdariffa 2019. Roselle (Hibiscus sabdariffa L.), a traditional herbal medicine, has shown significant clinical anti-hyperglycemic efficacy. However, the mechanism of the treatment is not yet clear. We found that Roselle has a certain protective effect on vascular endothelial cells through this study. This study was based on network pharmacology and experimental validation. The present study made a comprehensive analysis by combining active ingredient screening, target prediction and signaling pathway analysis to elucidate the active ingredients and possible molecular mechanism of roselle for the first time, which provided theoretical and experimental basis for the development and application of roselle as an antidiabetic drug. Highlights: Diabetic vasculopathy is one of the major causes of death in patients with diabetes, and hyperglycemia is an important cause of diabetic vascular lesions. Roselle (Hibiscus Sabdariffa L), a traditional herbal medicine, has shown significant clinical efficacy against hyperglycemia. We found that Roselle has a certain protective effect on vascular endothelial cells through this study. The present study made a comprehensive analysis by combining active ingredient screening, target prediction and signaling pathway analysis to elucidate the active ingredients and possible molecular mechanism of roselle for the first time.